Transcriptome mining for phylogenetic markers in a recently radiated genus of tropical plants (Renealmia L.f., Zingiberaceae) (2018)
The reconstruction of relationships within species-rich groups that have recently evolved in biodiversity hotspots is hampered by a lack of phylogenetically informative markers. It is also made difficult by the lack of sampling necessary to reconstruct a species-level phylogeny. We use transcriptome mining to search for markers to reconstruct a phylogeny of the amphi-Atlantic genus Renealmia L. f. (Zingiberaceae). We recover seven introns from single copy genes and use them to reconstruct the phylogeny of the genus together with a commonly used phylogenetic marker, internal transcribed spacers of ribosomal DNA (ITS) that has previously been used to reconstruct the phylogeny of the genus. We targeted genes with low numbers of base pairs that improves sequencing success using highly degraded DNA from herbarium specimens. The use of herbarium specimens greatly increased the number of species in the study as these were readily available in historical collections. Data were obtained for 14 of the 17 African species and 54 of the 65 Neotropical species. The phylogeny was well-supported for a number of Renealmia subgroups although relationships among those clades remained poorly supported.